Safety of early feeding after endoscopic ultrasound-guided fine needle biopsy: a retrospective study - Bo Kyeong Lee; Byung Soo Kwan; Kwang Min Kim; Sang Goon Shim; Jung Won Lee; Jun Young Kim; Bo Ram Sung; Hye In Kim; Seung Hwan Kim (BMC Gastroenterology)
Abstract Background Endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) is a widely utilized and relatively safe procedure for diagnosing pancreatic diseases. Although early feeding post-EUS-FNB is clinically advantageous, consensus regarding the optimal feeding time in current guidelines remains lacking. Therefore, this study aims to evaluate the efficacy and safety of early feeding after EUS-FNB. Methods A retrospective analysis was conducted on 111 patients who underwent EUS-FNB for diagnosing pancreatic diseases between January 1, 2021, and March 31, 2022, at Samsung Changwon Hospital. Patients were divided into two groups: those who fed within 4 h after the procedure and those who remained fasting for 24 h after the procedure. We investigated two hospitalization duration metrics: procedure-related hospital days (HD), defined as the period exclusively attributed to EUS-FNB recovery, and total HD, encompassing the entire hospitalization duration, including additional diagnostic or therapeutic interventions unrelated to the procedure. Results After excluding missing data, 110 patients were analyzed. Among them, the mean age was 67.4 years, with 52.7% being male. Of these, 42 patients resumed early feeding. No significant difference was observed between the two groups in terms of complications. However, the procedure-related HD was shorter in the early feeding group (3.8 ± 0.8 vs. 4.9 ± 0.7 days, P = 0.001). Additionally, the multivariate analysis revealed no difference in complication rates between the two groups (odds ratio; 0.83, 95% confidence interval; 0.07–9.39, P = 0.877). Conclusions Early feeding following EUS-FNB was associated with a shorter hospitalization stay without increasing the risk of complications. These findings suggest that early feeding after EUS-FNB offers clinical benefits.